Faktor-Faktor yang Mempengaruhi Persentase Penduduk Miskin di Indonesia Tahun 2015-2018 Menggunakan Regresi Data Panel - Ian Tryaldi Halim; Annisa Putri Ramadhanty; Dewi Retno Oscarini; Galang Madya Putra; Helen Fricylya Br Tobing; Rani Nooraeni (Engineering, MAthematics and Computer Science (EMACS) Journal, 2020)
Indonesia as a country rich in natural resources has not been able to make it as a country that is free from poverty. The percentage of poor people in Indonesia is still high, is still less efficient, the government's policy in alleviating poverty. This can be seen from the increase in the human development index, gross domestic product and the number of health facilities that are not counted by reducing the percentage of the poor population. The purpose of this study is to describe the percentage of poor people in Indonesia and to analyze the factors that influence the percentage of poor people in Indonesia. This study uses panel data regression analysis using the Random Effect Model (REM) method. The results showed the regional gross domestic product and the level of openness significantly open to the percentage of Indonesia's poor population. While the human development index and the amount of health development are not significant to the percentage of poor people in Indonesia. From the results of this study, Indonesia can optimize employment opportunities that can be released so that it can improve the state of the country. This implementation is expected to increase the number of poor people in Indonesia which can be significant.